3D printed bioactive composite scaffolds for bone tissue engineering - OKTAR, FAİK NÜZHET; ŞENGÖR, MUSTAFA; GÜNDÜZ, OĞUZHAN (Elsevier B.V., 2020)
Bone health and regeneration is crucial to human survival. With the advancement in the bone research area, bone implants have been under scrutiny to find a better material that could help in bone regeneration and growth. A wide range of material has been studied and examined to find the ideal combination. In this paper, a new blend of Tri-calcium phosphate (TCP), polycaprolactone (PCL) and bovine hydroxyapatite (BHA) was introduced to create scaffolds with fused deposition 3d printing. Effect of BHA concentration as a naturally derived and newcomer 3d printing material was investigated via FTIR, XRD, and SEM analyses. In vitro studies were exhibited that 15% (wt/wt) BHA fabricated composite scaffolds possessed more bioactivity than other cases with increasing proliferation and growth rates. © 2019 Elsevier B.V.
Keywords: 3D printing; Bone scaffold; Calcium phosphate; Hydroxyapatite; Polycaprolactone